2017
DOI: 10.1016/j.jneumeth.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Method for testing sustained attention in touchscreen operant chambers in rats

Abstract: Background Sustained attention, the ability to detect rare and unpredictable events, is central to cognitive performance. This construct can be tested in rodents using a Sustained Attention Task (SAT), where rats are trained to detect an unpredictably occurring signal (a brief light presentation) from non-signal events. The traditional version of this task utilizes an operant chamber with a central panel light for the signal and two retractable response levers. Adaptation of SAT to the increasingly popular tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A failure to make any response during the response window counts as an omission. To expand the availability of SAT, we recently modified the task for touchscreen operant chambers, in which one wall is a touchscreen that can both display visual stimuli and record nose-poke responses 19 . Touchscreen chambers are becoming popular because of their versatility to run a variety of tasks (e.g., paired associate learning, reversal learning, etc.)…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A failure to make any response during the response window counts as an omission. To expand the availability of SAT, we recently modified the task for touchscreen operant chambers, in which one wall is a touchscreen that can both display visual stimuli and record nose-poke responses 19 . Touchscreen chambers are becoming popular because of their versatility to run a variety of tasks (e.g., paired associate learning, reversal learning, etc.)…”
mentioning
confidence: 99%
“…Similar to other touchscreen procedures 20,21,22 , our adaptation of SAT requires the use of an opaque plastic touchscreen cover, called a mask, with holes cut into it. A central, circular hole allows for the presentation of a signal by presenting a white stimulus on the screen behind it, and two square response areas, one designated for hits and one for CRs, allow the rat to make touch responses 19 . In the traditional chambers, the 4-s response window is typically indicated with the presentation of the levers, but a previous study demonstrated that a tone can also be used to signal the response window 23 .…”
mentioning
confidence: 99%
See 3 more Smart Citations